Mapping the Distribution of Invasive Alien Species Acacia (Accacia decurrens) in Thekelan Hiking Trail Area, Kopeng Resort, Mount Merbabu National Park - Ashila, Jilan; Safitri, Fauziana Erlis; Hermawan, Bagus; Febrian, Ardhitya Rio; Ramadhan, Auriga Wahyu Widyadana; Sunarhadi, Muhammad Amin (Universitas Veteran Bangun Nusantara, 2023)
Kopeng Resort is one of Mount Merbabu National Park resorts located in Getasan District, Semarang Regency, Central Java. Where in this area, there is a hiking trail called Thekelan. Besides that, Mount Merbabu National Park has problems regarding invasive alien species, one of which is the Acacia plant (Accacia decurrens) which also grows on the Thekelan hiking trail. Therefore, this study aims to determine the spatial distribution of invasive plants in the Mount Merbabu National Park area located in the Kopeng Resort area. The data collection method used in this study was using GPS’s survey where if you find an acacia plant, you will mark it or dots so that later the output will be a kml file which can be processed in the ArcGIS software. The data processing method uses Arcgis software so that it is in the form of a map, and the height of the acacia plant points will be known. The results showed that the distribution of acacia plants in the area around the climbing route of Mount Merbabu Thekelan was classified as very dense at an altitude of 1,847 masl to 2,153 masl with moderate to steep slopes. Whereas at altitudes ranging from 2,153 to the peak, which has very steep slopes, the density of acacia decreases. 153 meters above sea level with moderate to steep slopes.